Penerapan Model Discovery Learning Berbantuan Geogebra Untuk Meningkatkan Hasil Belajar Siswa Kelas XI MIA SMAN 1 Wulla Waijelu Kabupaten Sumba Timur Pada Materi Lingkaran - Tamu Ama, Soleman; Krisnandari Ekowati, Ch.; K. S. Blegur, Irna (Griya Journal of Mathematics Education and Application, 2024)
This research was motivated by the low learning outcomes of class XI MIA at SMAN 1 Wulla Waijelu, East Sumba Regency on circle material. The aim of this research is to describe the application of the geogebra-assisted discovery learning model to improve the learning outcomes of class XI MIA students at SMAN 1 Wulla Waijelu, East Sumba Regency on circle material. The research method used is Classroom Action Research (PTK), with qualitative and quantitative data types. This research was carried out in class XI MIA at SMAN 1 Wulla Waijelu, East Sumba Regency, totaling 22 students. Data collection techniques in this research were through observation, tests and questionnaires, with the instruments used namely teacher and student observation sheets, test questions and student response questionnaires. Implementation of this Classroom Action Research has 4 stages, namely 1) Planning; 2) Implementation of action (action); 3) Observation; 4) Reflection. The research results show that the percentage of completeness of students' classical learning outcomes at the end of cycle I reached 85.71%, which meets the success indicators of this research. The implementation of the teacher ability level score (TKG) in cycle I reached 93.96 and was in the very good category. In addition, the implementation score of student activities in cycle I reached 88.33 and was in the very good category.